BUDAYA PEMBELAJARAN ORGANISASI DAN PROSES PEMBELAJARAN ORGANISASI SERTA PENGARUHNYA TERHADAP KINERJA ORGANISASI DAN KINERJA BERKELANJUTAN DI PERGURUAN TINGGI - Arini, Arini; Masirun; Dwika Lodia Putri; Farwitawati, Reni (Komunitas Manajemen Kompetitif, 2025)
This study aims to analyze the influence of organizational learning culture on organizational performance and sustainable performance, with the organizational learning process as a mediating variable. A quantitative approach was employed by conducting a survey of lecturers at universities in Riau Province, and the data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The findings reveal that the organizational learning culture has a significant effect on the organizational learning process, which in turn enhances both organizational performance and sustainable performance. Furthermore, the organizational learning process is proven to mediate the relationship between organizational learning culture and organizational performance. These results support the Natural Resource-Based View (NRBV) theory, which positions organizational learning as a strategic resource that is difficult to imitate and serves as a source of long-term competitive advantage. This study is limited by its sample, which only covered universities in Riau Province, its cross-sectional design, and the restricted scope of variables. Future research is suggested to expand the sample coverage, employ longitudinal designs, and include additional variables such as transformational leadership, innovation, and the adoption of digital technologies. Theoretically, this study contributes to the enrichment of organizational learning literature in higher education, while practically it provides implications for university leaders to foster a learning culture that promotes openness, collaboration, and knowledge management in order to improve academic quality, governance, and organizational sustainability